A review of al-Qaradawi’s book “Islam: the future civilization” - Abdul Razak, Mohd Abbas; Machouche, Salah (2023)
This book by the late Dr Yusuf Al-Qaradawi (1926-2022) is a book that critically analyses the positive and negative aspects of Western civilization and offers the Islamic worldview that can save the masses in the West. At the very outset of his book, Al-Qaradawi gives some descriptive nature of what a civilization is all about. In a similar fashion to any other expert on civilizational studies, Al-Qaradawi states that a civilization like a human being has a body and soul. According to him, the body of a civilization can be referred to monumental buildings, factories, a proper system of governance and all other infrastructures that facilitate better living conditions for the citizens that live within a particular civilization. As for the soul of a civilization, he refers to those things that are intangible and artistic in nature like value system, ideas, ideals, religion, poetry, etc.